Dual mechanism of vascular endothelial growth factor upregulation by hypoxia in human hepatocellular carcinoma. Issue 1 (1st January 2001) - Marschall, Z von; Cramer, T; Höcker, M; Finkenzeller, G; Wiedenmann, B; Rosewicz, S
Abstract : BACKGROUND/AIMS: Vascular endothelial growth factor (VEGF) plays a key role in regulation of tumour associated angiogenesis. In the current study we analysed expression of VEGF and its receptors in human hepatocellular carcinoma (HCC) and investigated the molecular mechanisms of VEGF regulation by hypoxia. METHODS: VEGF, kinase domain region (KDR)/fetal liver kinase 1 (flk-1), and flt-1 expression were examined by immunohistochemistry and in situ hybridisation in 15 human HCC tissues. Expression of VEGF and regulation by hypoxia were assessed in three human HCC cell lines using a quantitative competitive reverse transcription-polymerase chain reaction, ELISA, and a series of 5′ deletion reporter gene constructs of the human VEGF promoter in transient transfection assays. RESULTS: We observed over expression of VEGF mRNA and protein in HCC compared with cirrhosis or normal liver. Expression of VEGF in tumour cells was strongly increased in areas directly adjacent to necrotic/hypoxic regions. Both VEGF receptors were detected in vascular endothelia of HCC while only KDR/flk-1 receptors were detected in endothelial cells of cirrhotic livers. Expression of VEGF was observed in all human HCC cell lines examined. Hypoxia (1% oxygen) resulted in profound upregulation of VEGF mRNA and protein levels. Furthermore, hypoxia treatment resulted in a doubling of VEGF mRNA stability. Deletion analysis of the human VEGF 5′ flanking region −2018 and +50 demonstrated induction of VEGF promoter activity under hypoxic conditions which was significantly decreased following deletion of the region −1286 and −789 suggesting a substantial contribution of the −975 putative hypoxia inducible factor 1 binding site to hypoxia mediated transcriptional activation of the VEGF gene. CONCLUSION: These data suggest hypoxia as a central stimulus of angiogenesis in human HCC through upregulation of VEGF gene expression by at least two distinct molecular mechanisms: activation of VEGF gene transcription and an increase in VEGF mRNA stability.